A comprehensive review of the genetic control of cooking time in dry beans (Phaseolus vulgaris L.) - Hannah R. Jeffery; Marcelo Efrén Murillo‐Quesada; Luis Barboza‐Barquero; Karen Cichy (Plants, People, Planet)
Societal Impact Statement Reducing cooking time could increase dry beans (Phaseolus vulgaris) consumption. Cooking is an essential processing step needed to unlock the nutrients in dry beans and to make them palatable and safe for consumption. Long cooking times have consequences for dry bean use, especially where cooking fuel cost is high and when people prefer foods that are more convenient to prepare. Understanding the genetic control and genetic diversity for cooking time along with the nutritional tradeoffs will help to breed nutritious bean varieties with shorter cooking times, thereby making dry beans more accessible to consumers around the world. Summary Dry beans generally require long cooking times, and this influences their utilization and acceptability as a food source. Fuel usage, water usage, and convenience are three constraints associated with cooking beans. The cooking times of dry beans are dependent on many factors including growing conditions, post‐harvest handling and storage, cooking methods, and genotype. While there have been significant research endeavors to elucidate how post‐harvest storage and handling influence cooking time, there has been comparatively less research on the genetic regulation of cooking time. This review provides an in‐depth examination of the genetic control of cooking time in dry beans, including genetic mapping studies and its implications for breeding purposes. Further, the available physiological and post‐harvest research is summarized and evaluated in the context of understanding genetic and environmental factors that affect the cooking times of dry beans. The current evidence suggests that cooking time is increased by genetic factors that decrease the amount of soluble compounds in the cotyledons, including but not limited to 1) genes that increase the abundance of calcium‐binding storage proteins and/or de‐methylesterfied pectins paired with high inter‐ or intra‐cellular calcium levels (higher calcium levels can be caused by reduced levels of phytate) and 2) genes that increase insoluble condensed tannin/lignin content in the cotyledon cell walls. Identifying genetic factors that contribute to cooking times across a range of environments could aid breeding efforts to develop reliably fast‐cooking varieties in different dry bean market classes, thereby making dry beans more accessible to consumers around the world.